Public Health Crisis during COVID-19 pandemic - David Gaus (Fundación Salud y Desarrollo Andino, Saludesa Ecuador, 2021)
During the COVID pandemic, biomedicine and the rapid development of anti-COVID vaccines has been widely praised, while the global public health response has been questioned. Fifteen United States based combined experts in primary healthcare and public health responded to an open question focusing on this issue. Eleven of these experts responded. Four major themes emerged from their answers, including: fragmentation between public health and biomedicine; underfunding of public health; lack of centralized public health authority; business interests over the public good and well-being.